THE IMPLEMENTATION OF GOOGLE CLASSROOM TO TEACH ENGLISH AT SMPN 2 NGRONGGOT IN PANDEMIC ERA COVID19 - Safitri, Handayani Eki; Kurniawan, Erwin Hari (Jurnal Pendidikan Bahasa Inggris Proficiency, 2021)
The purpose of this study is to know how is the implementation of Google Classroom to teach English at SMPN 2 Ngronggot in pandemic era COVID 19 . Doing learning by using Google Classroom there are many advantages and disadvantages for all of the user excatly IX students at SMPN 2 Ngronggot.This study focused on four aspect. Teacher preparation, implementation of teaching, evaluation and the last students response. The reseacher use four instruments are interview, observation, documentation and students response. For preparation the teacher use lesson plan when she teach the students, for implementation the teacher also use English when she explain the material and sometimes the teacher use Indonesian because not all of the students understand what the teacher said to them, for evaluation the teacher give conclussion for material which them and sometimes the teacher give them homework and they must sumbit in Google Classroom and for the last students response some students still difficulty to use Google Classroom because they think this is new learning.The result of this research is implementation by using Goggle Classroom can be the first method to teach online learning at SMPN 2 Ngronggot and this research also reccomended for, first the students as the students should have motivation although there are many obstacless using Google Classroom one of it is limit in access internet, the handphone is broke or did not have mobile phone but the student must try to join with their friend in order to all of the material can be known, for the teacher should give another ways in order the all of students can follow the material and for next the readers teaching by using Google Classroom can be motivate to others.